EFFECT OF TRUST, PROMOTION, AND PRICE ON CUSTOMER LOYALTY OF GRAB APPLICATION USERS (CASE STUDY ON STUDENTS AT UNIVERSITAS PRIMA INDONESIA, MEDAN) - Fenny Krisna Marpaung; Dennis Hermawan (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2022)
The purpose of this study is to analyze effect of trust, promotion, and price on customer loyalty of Grab application users, case study on students at Universitas Prima Indonesia, Medan. This research is a quantitative descriptive research. The population of this research is all Universitas Prima Indonesia students who use the Grab application. The sampling technique uses simple random sampling. So the sample in this study was 96 respondents. The data analysis technique used multiple linear regression. Multiple linear regression consists of partial (t) and simultaneous (F) hypothesis testing. The results showed that trust has a positive and insignificant effect on customer loyalty. Promotion has a positive and significant effect on customer loyalty. Price has a positive and significant effect on customer loyalty. Trust, promotion, and price have a significant effect together on customer loyalty.